Numerical Analysis and Structure Improvement for the Corrosion and Cracking of the Mixing Tee for the Quenching Gas of Hydrogen from Coal. (2015) - Gao, B.J.; Li, H.J.; Chen, Y.F.; Dong, J.H.
Abstract: The gully shape thinning due to corrosion often occurs in the cold and hot syngases mixing tee and its downstream straight pipe used in the gas quenching system of the coal gasification process, and leads to leakage and cracking of the pipe which endangers the system safety. Analysis indicates that droplets in the cold syngases turn out to be corrosive droplets when absorbing H2 S and CO2 at working pressure and temperature. In this paper, the flow, aggregation and evaporation of the corrosive droplets are simulated with the k - ɛ turbulence model, the species transport model and the discrete phase model by FLUENT. It reveals that the corrosive droplets would aggregate to the downstream of the mixing tee at 0 o orientation. The distance of the downstream aggregation is 1.5 m. The aggregation and evaporation of corrosive droplets causes the corrosion thinning of the droplet aggregation region, which leads to tear cracking under high stress. An improved structure is proposed to avoid the corrosive droplet aggregation, in which a fluid guidance is conically flared and welded before the branch entrance. The fluid guidance is made of Inconel8825. The cold syngases flow inside the fluid guidance, and the hot syngases flow outside the fluid guidance. The cold and hot fluid exchanges heat through the guidance but without mixing. The mixing is postponed to the downstream. It shows that the aggregation of the corrosive droplet is effectively eliminated and droplet concentration at the downstream wall is less an order of magnitude of the upstream, which is helpful to avoid the corrosion and cracking of the structure.